Mesoscale Interrogation Reveals Mechanistic Origins of Lithium Filaments along Grain Boundaries in Inorganic Solid Electrolytes. Issue 3 (15th December 2021) - Vishnugopi, Bairav S.; Dixit, Marm B.; Hao, Feng; Shyam, Badri; Cook, John B.; Hatzell, Kelsey B.; Mukherjee, Partha P.
Abstract: Solid‐state batteries (SSBs), utilizing a lithium metal anode, promise to deliver enhanced energy and power densities compared to conventional lithium‐ion batteries. Penetration of lithium filaments through the solid‐state electrolytes (SSEs) during electrodeposition poses major constraints on the safety and rate performance of SSBs. While microstructural attributes, especially grain boundaries (GBs) within the SSEs are considered preferential metal propagation pathways, the underlying mechanisms are not fully understood yet. Here, a comprehensive insight is presented into the mechanistic interactions at the mesoscale including the electrochemical‐mechanical response of the GB‐electrode junction and competing ion transport dynamics in the SSE. Depending on the GB transport characteristics, a highly non‐uniform electrodeposition morphology consisting of either cavities or protrusions at the GB‐electrode interface is identified. Mechanical stability analysis reveals localized strain ramps in the GB regions that can lead to brittle fracture of the SSE. For ionically less conductive GBs compared to the grains, a crack formation and void filling mechanism, triggered by the heterogeneous nature of electrochemical‐mechanical interactions is delineated at the GB‐electrode junction. Concurrently, in situ X‐ray tomography of pristine and failed Li7 La3 Zr2 O12 (LLZO) SSE samples confirm the presence of filamentous lithium penetration and validity of the proposed mesoscale failure mechanisms. Abstract : The morphological stability of lithium metal electrodes in solid‐state batteries remains a major challenge. In this work, the electrochemical‐mechanical interactions and competing ion transport dynamics underlying the stability of grain boundary‐electrode junctions is examined. A mechanistic failure pathway including cavity growth and strain hotspot evolution is triggered due to the ionic transport mismatch between the grains and grain boundaries.